Sekolah dengan konsep pendidikan humanis - Sabaruddin, Sabaruddin (Universitas Negeri Yogyakarta, 2020)
Education is a shared duty and responsibility to develop awareness and insight between humans to continue life. Efforts to increase awareness, children's personality, and develop creativity gave birth to an educational approach called